Dinamika Proses Penyelenggaraan Pemilihan Walikota di Kota Makassar Tahun 2018 - Siti Nurhasanah Furqani Furqani; A. Lukman Irwan Irwan; Juanda Nawawi Nawawi (Departemen Ilmu Pemerintahan Fisip Unhas, 2020)
This research aims to assess and analyze the dynamics that occurred in the process of electoral mayor in Makassar City in 2018. The type of research used in this study is qualitative, which will provide a factual representation of the purpose of research. The results of this study show that: there are problems and dynamics that occur in several phases. As at the stage of verification of individual candidate support that there is a chairman of PPS who commits violations and unneutrality ASN. In the stage of setting the candidate is also quite dynamic where the dispute occurs between the elections of the mayor and organizers. At the campaign stage, the APPI-CICU pair is not intense reporting its campaign activities. Then, in the stage of voting and counting, there is a form of the disintegration of the organizers of the district PPK Tamalate that manipulates the data of sound results. As for the stage of determination of candidates elected, KPU Kota Makassar announced it will conduct the election of the mayor back in 2020 because the couple APPI-CICU was defeated by the acquisition of empty columns